The Attenuation of Chronic Ulcerative Colitis by (R)-salbutamol in Repeated DSS-Induced Mice. (7th February 2022) - Deng, Liangjun; Guo, Haihua; Wang, Shanping; Liu, Xiaoming; Lin, Yue; Zhang, Rui; Tan, Wen
Abstract : Racemic salbutamol ((RS)-sal), which consist of the same amount of (R)-sal and (S)-sal, has been used for asthma and COPD due to its bronchodilation effect. However, the effect of (R)-sal on repeated dextran sulfate sodium (DSS)-induced chronic colitis has not yet been investigated. In this study evaluated the potential effect of (R)-, (S)-, and (RS)-sal in mice with repeated DSS-induced chronic colitis and investigated the underlying mechanisms. Here, we verified that chronic colitis was significantly attenuated by (R)-sal, which was evidenced by notably mitigated body weight loss, disease activity index (DAI), splenomegaly, colonic lengths shortening, and histopathological scores. (R)-sal treatment noticeably diminished the levels of inflammatory cytokines (such as TNF- α, IL-6, IL-1 β, and IFN- γ ). Notably, the efficacy of (R)-sal was better than that of (RS)-sal. Further research revealed that (R)-sal mitigated colonic CD4 leukocyte infiltration, decreased NF- κ B signaling pathway activation, improved the Nrf-2/HO-1 signaling pathway, and increased the expression of ZO-1 and occludin. In addition, (R)-sal suppressed the levels of TGF- β 1, α -SMA, and collagen in mice with chronic colitis. Furthermore, the 16S rDNA sequences analyzed of the intestinal microbiome revealed that (R)-sal could mitigate the intestinal microbiome structure and made it more similar to the control group, which mainly by relieving the relative abundance of pathogens (such as Bacteroides) and increasing the relative abundance of probiotics (such as Akkermansia). Therefore, (R)-sal ameliorates repeated DSS-induced chronic colitis in mice by improving inflammation, suppressing oxidative stress, mitigating intestinal barrier function, relieving intestinal fibrosis, and regulating the intestinal microbiome community. These results indicate that (R)-sal maybe a novel treatment alternative for chronic colitis.